Diversity of Wood-Decaying Fungi in Wuliangshan Area, Yunnan Province, P.R. China - Xiao He; Chang-Lin Zhao (Diversity, 2022)
Five surveys were carried out in the Wuliangshan area, Yunnan Province, P.R. China, based on a combination of morphological features and molecular evidence. Around 2454 specimens of wood-decaying fungi were collected. The paper summarizes the obtained results on the wood-decaying fungi of this area, consisting in 95 species distributed in 59 genera, 23 families and 9 orders. Their hosts and substrates were also identified. A checklist of wood-decaying fungi is given. Sequences of the ITS nrRNA gene region of the studied specimens were generated and phylogenetic analysis was performed with maximum likelihood, maximum parsimony and Bayesian inference methods. The present list of wood-decaying fungi enriches the knowledge of fungal diversity worldwide and supplies the basic data for future applications.